A Cost-Effectiveness Study of Antibiotic Drug Delivery System in Chronic Suppurative Otitis Media (CSOM) - Akram, Muhammad; Saud, Anshar; Arifin, Bustanul (Faculty of Pharmacy, Universitas Gadjah Mada, 2025)
Background: Chronic Suppurative Otitis Media (CSOM) is a chronic inflammatory and infectious disease of the middle ear or mastoid cavity that can result in the loss of bodily functions or even death. The higher concentration of CSOM is found in developing nations such as Indonesia, where the population cannot afford treatment. In cases of persistent otorrhea following 3 weeks of treatment with topical ear antibiotics, oral antibiotics may be considered as a second line of treatment. Topical ear antibiotics are insufficiently available at healthcare facilities because they are not included in the Indonesian National List of Essential Medicines (NLEM).Objectives: The objective of this study was to compare the cost-effectiveness of topical ear antibiotics versus oral antibiotics in the treatment of chronic suppurative otitis media (CSOM).Methods: This study was a cross-sectional study using retrospective data from medical records and cost assessments at a rural hospital in the Gowa district of South Sulawesi. The effectiveness of the treatments was evaluated based on the frequency of visits to the ENT department, with antibiotic prescriptions and positive otorrhea.Results: The findings revealed that the Average Cost-Effectiveness Ratio (ACER) for topical ear antibiotics was Rp 161,020, while the ACER for oral antibiotics was Rp 286,968. The Incremental Cost-Effectiveness Ratio (ICER) was determined to be Rp 351, and the Incremental Net Benefit (INB) was positive (Rp 99,857) at threshold Rp 434,500.Conclusion: Our study found that topical ear antibiotics were more cost-effective than oral antibiotics when considering the INB values based on INA-CBGs, along with fluctuations in cost-effectiveness using sensitivity analysis.